International Residency Program Directors on Implementing Educational Transformation: A Qualitative Study of Their Experiences and Strategies for Overcoming Challenges - Dutta D; Ibrahim H; Stadler D; Cofrancesco J; Nair SC; Archuleta S (Accreditation Council for Graduate Medical Education)
BACKGROUND: Residency program directors (PDs) need to navigate diverse roles and responsibilities as clinical teachers, administrators, and drivers of educational improvement. Little is known about the experience of PDs leading transformation of international residency programs. OBJECTIVE: We explored the lived experiences of international residency PDs and developed an understanding of how PDs manage educational program transformation. METHODS: Using a phenomenological approach, semi-structured interviews were conducted with current and former PDs involved in the transformation to competency-based medical education in the first international settings to be accredited by the Accreditation Council for Graduate Medical Education-International (ACGME-I). Thirty-three interviews with PDs from Qatar, Singapore, and the United Arab Emirates were conducted from September 2018 to July 2019, audio-recorded, and transcribed. Data were independently coded by 2 researchers. A thematic analysis was conducted and patterns that reflected coping and managing educational reform were identified. RESULTS: PDs described distinctive patterns of navigating the educational transformation. Five themes emerged: PDs (1) embraced continuous learning and self-development; (2) managed change in the context of their local settings; (3) anticipated problems and built support networks to effectively problem-solve; (4) maintained relationships with stakeholders for meaningful and constructive interactions; and (5) focused on intrinsic qualities that helped them navigate challenges. CONCLUSIONS: International PDs were presented with significant challenges in implementing educational transformation but coped successfully through distinctive patterns and methods.
Keywords: Accreditation; Education, Medical, Graduate; Humans; Internship and Residency; Learning; Qualitative Research; 1302 Curriculum and Pedagogy